Measuring and Mitigating the Costs of Stockouts - Anderson, Eric T.; Fitzsimons, Gavan J.; Simester, Duncan (Management Science, 2006)
There is now an extensive theoretical literature investigating optimal inventory policies for retailers. Yet several recent reviews have recognized that these models are rarely applied in practice. One explanation for the paucity of practical applications is the difficulty of measuring how stockouts affect both current and future demand. In this paper, we report the findings of a large-scale field test that measures the short- and long-run opportunity cost of a stockout. The findings confirm that the adverse impact of a stockout extends to both other items in the current order as well as future orders. We show how the findings can be used to provide input to inventory planning models and illustrate how failing to account for the long-run effects of a stockout will lead to suboptimal inventory decisions. We also demonstrate how the findings can be used in a customer lifetime value model. Finally, the study investigates the effectiveness of different responses that firms can offer to mitigate the cost of stockouts. There is considerable variation in the effectiveness of these responses. Offering discounts to encourage customers to backorder rather than cancel their orders is widely used in practice, but that was the least profitable of the responses that we evaluated. The findings have important implications for retailers considering the use of discounts as a response to stockouts.